PENAL POPULISM - ORIGIN, DEVELOPMENT AND FUTURE - Kovacevic, Milica D.; Atanasov, Saša (Politeia, 2025)
During the last few decades, penal populism has been one of the continuously present criminal political trends globally. Propositions of penal populism could be briefly reduced to stricter punishment for offenders, allegedly in accordance with the attitudes and wishes of the wider public. The problems of penal populism concern its scientific and empirical lack of foundation, i.e. the lack of concrete argumentation when devising inventive solutions, as well as the lack of consultation with the professional public. Therefore, the authors tried to point out the basic assumptions and practical implications of penal populism through the analysis of the literature, with the aim of introducing the concept to the wider public and opening space for debate. By summarizing the experiences of comparative law, with a special focus on Serbia, the authors point out that despite the significant socio-economic differences, the positions of penal populism largely coincide in different parts of the world. Scientific methods of content analysis, normative-logical and comparative legal methods were applied. The authors conclude that penal populism will not just disappear, and that it should therefore be recognized and studied in order to develop future criminal policies in accordance with the dynamics and structure of criminality, but also with adequate consideration of public attitudes and opinions.